In Vitro Inhibition of Cytochrome P450 3A4 by Aronia melanocarpa Constituents - Bräunlich, Marie; Christensen, Hege; Johannesen, Siri; Slimestad, Rune; Wangensteen, Helle; Malterud, Karl E.; Barsett, Hilde (Planta Medica, 2013)
Extracts, subfractions, isolated anthocyanins and procyanidins, and two phenolic acids from aronia [Aronia melanocarpa] were investigated for their CYP3A4 inhibitory effects, using midazolam as the probe substrate and recombinant insect cell microsomes expressing CYP3A4 as the enzyme source. Procyanidin B5 was a considerably stronger CYP3A4 inhibitor in vitro than the isomeric procyanidin B2 and comparable to bergamottin, a known CYP3A4 inhibitor from grapefruit juice. The inhibitory activity of proanthocyanidin-containing fractions was correlated to the degree of polymerization. Among the anthocyanins, cyanidin 3-arabinoside showed stronger CYP3A4 inhibition than cyanidin 3-galactoside and cyanidin 3-glucoside. Thus, the ability to inhibit CYP3A4 in vitro seems to be influenced by the sugar unit linked to the anthocyanidin.
Keywords: Aronia melanocarpa – Rosaceae; anthocyanins; procyanidins; phenolic acids; cytochrome P450 3A4